2020
DOI: 10.3390/pr8020132
|View full text |Cite
|
Sign up to set email alerts
|

Prickly Pear Seed Oil by Shelf-Grown Cactus Fruits: Waste or Maste?

Abstract: The chemical composition and properties of seed oils have attracted researchers nowadays. By this meaning, the physicochemical and bioactivity profile of prickly pear seed oil (PPSO) (a product of prickly pear fruits waste) were investigated. Seeds of shelf-grown cactus fruits (Opuntia ficus indica L.) were subjected to analysis. Moisture content (gravimetric analysis), seed content (gravimetric analysis), oil yield (Soxhlet extraction/gravimetric analysis), volatile compounds (HS-SPME/GC-MS), fatty acids prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
4
28
1
Order By: Relevance
“…The results demonstrated a significant antioxidant property of this seed oil, which is superior to the ascorbic acid and butylated hydroxytoluene (BHT) used as references [22]. Also, in another work, the seed oil from O. ficus-indica showed a high antioxidant activity in vitro (84.00±0.01%) [38]. The red and yellow O. ficus--indica seed oils obtained using Soxhlet as an extraction .019 μg/ml).…”
Section: Antioxidant Effectmentioning
confidence: 80%
See 2 more Smart Citations
“…The results demonstrated a significant antioxidant property of this seed oil, which is superior to the ascorbic acid and butylated hydroxytoluene (BHT) used as references [22]. Also, in another work, the seed oil from O. ficus-indica showed a high antioxidant activity in vitro (84.00±0.01%) [38]. The red and yellow O. ficus--indica seed oils obtained using Soxhlet as an extraction .019 μg/ml).…”
Section: Antioxidant Effectmentioning
confidence: 80%
“…4) [10]. In another study, it was shown that O. ficus-indica seed oil consists of a total phenolic content of 551.0±0.3 mg GAE/L [38]. A study carried out by Khémiri et al on O. ficus-indica seed oil from Tunisia indicated that this oil has a carotenoid content of 10.520 mg/kg oil, total chlorophyll content of 4.57 mg/kg oil, a flavonoid content of 3.1 mg QE/g oil and total phenolic content of 26.5 mg GAE/g oil [39].…”
Section: Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyzed seed oil’s components demonstrated that it contains considerable amounts of linoleic acid and sterols (unsaturated fatty acids), such as β-sitosterol and the presence of γ-tocopherol (vitamin E) [ 2 ]. Additionally, the oil is characterized by the presence of other substances such as phenols, well known for their health benefit [ 3 , 4 ]. Several kinds of research on this plant’s fruit seed oil have shown that it has numerous activities such as antioxidant [ 5 ], hepatoprotective [ 6 ], antilipidemic, antidiabetic, and antidiabetogenic [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, γ -tocopherol is the only vitamin E present in this oil [ 3 ]. Besides, it is characterized by the presence of other components such as phenols [ 4 ]. All of which may contribute to human health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%